Standard specification for steel castings suitable for pressure service (American Society of Testing Materials, 2007)
This specification2 covers low-alloy steels and martensitic stainless steels in the normalized and tempered, or quenched and tempered, condition suitable for pressurecontaining parts. The weldability of the classes in this specification varies from readily weldable to weldable only with adequate precautions, and the weldability of each class should be considered prior to assembly by fusion welding